Antinociceptive activity of the new triple reuptake inhibitor NS18283 in a mouse model of chemotherapy‐induced neuropathic pain. (14th July 2014) - Hache, G.; Guiard, B.P.; Nguyen, T.H.; Quesseveur, G.; Gardier, A.M.; Peters, D.; Munro, G.; Coudoré, F.
Abstract Background Chronic neuropathic pain can lead to anxiety and depression. Drugs that block reuptake of serotonin, norepinephrine and/or dopamine are widely used to treat depression, and have emerged as useful drugs in the treatment of neuropathic pain. This study compared the acute antinociceptive effects of NS18283, a novel triple monoamine reuptake inhibitor (MRI) with indatraline, venlafaxine and escitalopram in a mouse model of neuropathic pain. Method Neuropathic pain‐like behaviours were induced in mice by repeated injections of oxaliplatin (OXA), and assessed using the von Frey hair test, the cold plate test and the thermal preference plate test. Anxio/depressive phenotype and antidepressant‐like properties of compounds were assessed by the novelty suppressed feeding test and the tail suspension test, respectively. Results In vivo microdialysis experiments showed that each MRI increased extracellular serotonin, norepinephrine and/or dopamine levels in the cingulate cortex, in agreement with their in vitro reuptake inhibitory properties. Indatraline (3 mg/kg) reversed the full repertoire of OXA‐induced neuropathic hypersensitivity. NS18283 (10 mg/kg) reversed OXA‐induced mechano‐hypersensitivity and cold allodynia. Venlafaxine (16 mg/kg) and escitalopram (4 mg/kg) only reversed cold allodynia and mechano‐hypersensitivity, respectively. All MRIs produced antidepressant‐like activity in anxio/depressive phenotype of OXA mice. Conclusions Acute administration of drugs that enhance the activity of serotonin, norepinephrine and dopamine neurotransmission within nociceptive pathways may provide a broader spectrum of antinociception than dual or selective reuptake inhibitors in animal models of neuropathic pain. Whether similar observations would occur after repeated administration of such compounds in an attempt to simulate dosing in humans, or be compromised by dopaminergic‐mediated adverse effects warrants further investigation.